Chronicle of an Environmental Disaster: Aculeo Lake, the Collapse of the Largest Natural Freshwater Ecosystem in Central Chile - Vergara-Egert, P; Alaniz-Baeza, A (Cambridge University Press, 2019)
[No abstract available]